Epidemiological Insights and Current Perspectives of Leprosy in Sri Lanka: A Narrative Review (Bangladesh Journal of Infectious Diseases, 2025)
Sri Lanka eliminated leprosy as a public health problem in 1995. From 2001 onward, the caseload remained stable followed by a gradual decline between 2014 and 2019. Except for the COVID-19 pandemic years, approximately 2,000 new cases have been consistently reported each year. This review examines Sri Lanka's historical leprosy control strategies, including social marketing campaigns and the integration of leprosy care into the general healthcare system, which contributed to the elimination of the disease. It also highlights the support provided by the WHO and the country's renewed commitment to ongoing control efforts. Despite significant progress, Sri Lanka continues to face challenges in leprosy control, including a rise in child cases and potential drug resistance, revealing gaps in surveillance and control efforts. The current leprosy situation is affected by delayed diagnoses, incomplete treatments, and disruptions from the COVID-19 pandemic, emphasizing the importance of resilient healthcare systems and targeted interventions. Looking forward, priorities include early detection, treatment adherence, addressing socio-economic factors, and investigating environmental and genetic contributors to transmission. Achieving the goal of zero leprosy in Sri Lanka by 2030, which is a realistic and attainable goal, will require reliable diagnostics, vaccine development, sustained public awareness, and ongoing innovation, vigilance, and collaboration.Bangladesh Journal of Infectious Diseases, June 2025;12(1):159-166